The Influence of Customer Experience and Brand Awareness on Customer Loyalty of the Muslim Fashion Brand Rabbani with Customer Retention as a Mediating Variable - Btari Mariska Purwaamijaya; Hagia Sofia; Syti Sarah Maesaroh (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study addresses inconsistent findings in previous research by analyzing the influence of customer experience and brand awareness on customer loyalty toward the Muslim fashion brand Rabbani, with customer retention as a mediating variable, grounded in the Stimulus-Organism-Response (S-O-R) framework. A quantitative survey of 257 Rabbani customers in Tasikmalaya,  Indonesia, was conducted using purposive sampling based on specific criteria: residing in Tasikmalaya, having monthly income, and purchasing Rabbani products at least once within the past year. Data were collected through an online questionnaire using a five-point Likert scale and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that customer experience demonstrates the strongest influence on customer retention (β = 0.517; T = 7.631; P = 0.000) and customer loyalty (β = 0.263; T = 3.816; P = 0.000). Brand awareness significantly affects customer retention (β = 0.328; T = 3.782; P = 0.000) but shows no direct effect on customer loyalty (β = 0.132; T = 1.373; P = 0.170). However, the effect becomes significant through full mediation of customer retention (β = 0.166; T = 2.886; P = 0.004). These findings validate the applicability of the S-O-R model in Muslim fashion contexts and resolve theoretical inconsistencies regarding brand awareness effects on loyalty. The results suggest that Rabbani should prioritize service excellence, implement retention-focused loyalty programs, and shift marketing resources from awareness campaigns toward personalized customer relationship management initiatives to reverse declining Top Brand Index performance and strengthen brand competitiveness in Indonesia's growing Muslim fashion market.